1996
DOI: 10.1073/pnas.93.23.13377
|View full text |Cite
|
Sign up to set email alerts
|

Three members of a novel small gene-family from Arabidopsis thaliana able to complement functionally an Escherichia coli mutant defective in PAPS reductase activity encode proteins with a thioredoxin-like domain and “APS reductase” activity

Abstract: Three different cDNAs, Prh-19, Prh-26, and Prh-43 [3-phosphoadenosine-5-phosphosulfate (PAPS) reductase homolog], have been isolated by complementation of an Escherichia coli cysH mutant, defective in PAPS reductase activity, to prototrophy with an Arabidopsis thaliana cDNA library in the expression vector YES. Sequence analysis of the cDNAs revealed continuous open reading frames encoding polypeptides of 465, 458, and 453 amino acids, with calculated molecular masses of 51.3, 50.5, and 50.4 kDa, respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(106 citation statements)
references
References 43 publications
3
103
0
Order By: Relevance
“…The mRNA expression of ATP sulfurylase and APS kinase was down-regulated by sulfate starvation in leaves. Expression of the halotorerant gene SAL1, which was characterized to be involved in dephosphorylation of 3Ј-phosphoadenosine 5Ј-phosphosulfate (PAPS) to APS (22), was also depressed in sulfate-starved leaves. From these results, it was indicated that the expression of the genes involved in sulfate assimilation is not coordinately regulated by sulfate starvation in plants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mRNA expression of ATP sulfurylase and APS kinase was down-regulated by sulfate starvation in leaves. Expression of the halotorerant gene SAL1, which was characterized to be involved in dephosphorylation of 3Ј-phosphoadenosine 5Ј-phosphosulfate (PAPS) to APS (22), was also depressed in sulfate-starved leaves. From these results, it was indicated that the expression of the genes involved in sulfate assimilation is not coordinately regulated by sulfate starvation in plants.…”
Section: Resultsmentioning
confidence: 99%
“…T21459) were not affected by sulfate deprivation in leaves. APR1 (21,22), recently identified to encode an APS reductase isoform responsible for the reduction of adenosine 5Ј-phosphosulfate (APS) to sulfite, increased ca. 5.5-fold in roots and 2-fold in leaves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two functional thioredoxin-like molecules of 14 and 16 kDa, one of them very similar to thioredoxin h, have also been isolated from the C. reinhardtii outer dynein arm (a flagellar protein complex) (Patel-King et al, 1996). Two very recent reports also indicate the presence of a thioredoxin/glutaredoxin moiety in the sequence of three different chloroplastic PAPS reductases (or APS reductase), the thioredoxin domain being also situated in the C-terminal part of the protein (Guttierez-Marcos et al, 1996;Selyat, Murillo & Leustek, 1996). This type of organization is unique to the plant enzymes, since in bacteria and cyanobacteria PAPS reductase uses exogenous thioredoxin as an electron donor instead (Niehaus, Gisselmann & Schwenn, 1992).…”
Section: Thioredoxin Active Site and Thioredoxin Related Proteins In mentioning
confidence: 99%
“…Members of the Trx family have a distinct Trx motif, whereas the Trx-like protein family has a second functional domain in addition to the Trx motif (9). Although Ͼ20 different types of Trx genes have been identified in the Arabidopsis genome, there are only a few Trx-like proteins, including the PKC-interacting cousin of Trx, glutaredoxin-related proteins, and protein disulfide isomerase (PDI), whose functions remain to be elucidated (10)(11)(12)(13). Among the proteins containing the Trx fold, 2-Cys peroxiredoxins (Prxs) have been shown to alter their conformation from low molecular weight (LMW) to high molecular weight (HMW) complexes in response to heat shock and radical stresses (14,15).…”
mentioning
confidence: 99%